Composition for sealing electronic device, film for sealing electronic device, and method for forming film for sealing electronic device

By using the (meth)acrylate-containing electronic device packaging composition and curing under a nitrogen environment, the problems of unstable dielectric constant and insufficient adhesion of the packaging film in the prior art are solved, and a packaging film with high stability and good adhesion are achieved.

CN119586359APending Publication Date: 2025-03-07KONICA MINOLTA INC
View PDF 25 Cites 0 Cited by

Patent Information

Application Number
CN202380054901.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-29
Filing Date
2023-07-28
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

In the prior art, when using ultraviolet cured electronic device packaging film, the relative dielectric constant will increase after being stored at an environment of 85°C, and the adhesion of the cured film is insufficient.

Method used

The electronic device packaging composition containing (meth)acrylate as the photopolymerizable monomer was used to cure it with irradiation of 395 nm ultraviolet rays under a nitrogen environment to form a packaging film with a curing rate of more than 80%, and the residue rate was measured by a differential heat-thermal gravity synchronization measurement device to be 3%.

Benefits of technology

An electronic device packaging film with good relative dielectric constant stability and good adhesion is achieved, which avoids the problem of rising dielectric constant and improves the mechanical characteristics and strength of the packaging film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005249417570000081
    Figure BDA0005249417570000081
  • Figure BDA0005249417570000121
    Figure BDA0005249417570000121
  • Figure BDA0005249417570000122
    Figure BDA0005249417570000122
Patent Text Reader

Abstract

This composition for encapsulating an electronic device contains a photopolymerizable monomer and a photopolymerization initiator, and when the photopolymerizable monomer is cured by irradiation with ultraviolet light having a wavelength of 395 nm at 1.5 Jcm-2 in a nitrogen atmosphere, the curing rate of a formed electronic device encapsulating film is 80% or more. And the residue rate of the electronic device sealing film based on a differential thermal-thermogravimetric synchronous measurement device (TG-DTA) is 3% or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composition for encapsulating electronic devices, an electronic device encapsulating film and a method for forming an electronic device encapsulating film, and in particular to a composition for encapsulating electronic devices which can obtain an electronic device encapsulating film having a stable relative dielectric constant and good adhesion. Background Art

[0002] For electronic devices, particularly organic electroluminescent devices (hereinafter also referred to as "organic EL devices" or "organic EL elements"), it has been proposed to cover the surface of the organic EL element with an encapsulation layer to prevent the organic materials and electrodes used from being degraded by moisture.

[0003] As a technology for encapsulating organic EL elements, for example, the technology described in Patent Document 1 discloses an organic EL element encapsulation ultraviolet curable resin composition, which can be formed by inkjet method, comprises an acrylic compound (A) and a photopolymerization initiator (B), and the relative dielectric constant of the cured product at a frequency of 100 kHz is 3.0 or less. It is believed that by using this technology, an organic EL encapsulation ultraviolet curable resin composition can be provided that can be formed by inkjet method and the cured product can be easily reduced in dielectric constant.

[0004] In addition, the technology described in Patent Document 2 discloses an ink composition comprising at least one inorganic filler having an average particle size of 1 to 30 nm as a first component, at least one monomer selected from (meth)acrylate monomers as a second component, and at least one polymerization initiator as a third component, wherein the total weight concentration of the first to third components is 98 to 100 weight percent relative to the total weight of the ink composition. It is believed that this technology can provide a cured film having high refractive index, transmittance, flexibility, and low relative dielectric constant.

[0005] However, according to the techniques described in the above-mentioned patent documents 1 and 2, although a cured film (cured product) with a low relative dielectric constant can be obtained, when the above-mentioned composition is cured under ultraviolet rays with a long wavelength of 395 nm, the dielectric constant of the cured film after being stored in an environment of 85° C. increases, and there is a problem in the stability of the relative dielectric constant. In addition, the adhesion of the cured film is insufficient, and a cured film with better adhesion is required.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2020-057580

[0009] Patent Document 2: International Publication No. 2018 / 051732 Summary of the invention

[0010] The present invention is made in view of the above problems and circumstances, and the problem to be solved is to provide a composition for electronic device encapsulation that can obtain an electronic device encapsulation film with good relative dielectric constant stability and adhesion. In addition, an electronic device encapsulation film using the composition for electronic device encapsulation and a method for forming the electronic device encapsulation film are provided.

[0011] In order to solve the above-mentioned problems, the inventors have studied the causes of the above-mentioned problems and found that by containing (meth)acrylate as a photopolymerizable monomer and making the curing rate of the packaging film cured by irradiation under specific environmental conditions and the residue rate measured by a differential thermal-thermogravimetric synchronous measuring device within a specific range, a composition for encapsulating electronic devices can be provided, which can obtain an electronic device encapsulating film (cured film) with good relative dielectric constant stability and adhesion. In addition, an electronic device encapsulating film using the composition for encapsulating electronic devices and a method for forming the electronic device encapsulating film are provided.

[0012] That is, the above-mentioned problems of the present invention are solved by the following means.

[0013] 1. A composition for encapsulating an electronic device, comprising a photopolymerizable monomer and a photopolymerization initiator,

[0014] contains (meth)acrylate as the photopolymerizable monomer,

[0015] In nitrogen environment, 1.5 J cm -2 When cured by irradiation with ultraviolet rays having a wavelength of 395 nm, the formed electronic device encapsulation film has a curing rate of 80% or more, and a residue rate of 3% or more as measured by a differential thermal-thermogravimetric analysis (TG-DTA) apparatus.

[0016] 2. The composition for encapsulating electronic components according to item 1, wherein the curing rate is 90% or more.

[0017] 3. The composition for encapsulating electronic components according to item 1, wherein the residue ratio is 5% or more.

[0018] 4. The composition for encapsulating electronic components according to item 1, wherein the residue ratio is 10% or more.

[0019] 5. The composition for encapsulating electronic devices according to item 1, wherein the composition is -2 When cured by irradiation with ultraviolet rays having a wavelength of 395 nm, the resulting electronic device encapsulation film has a relative dielectric constant of 3.1 or less.

[0020] 6. The composition for encapsulating an electronic device according to item 1, wherein the average number of (meth)acrylic groups of the photopolymerizable monomer contained in the composition for encapsulating an electronic device is within a range of 1.3 to 1.5.

[0021] 7. The composition for encapsulating an electronic device according to item 1, wherein the ratio of the methacrylate of the photopolymerizable monomer contained in the composition for encapsulating an electronic device is within a range of 50 to 80%.

[0022] 8. An electronic device encapsulating film, which is an electronic device encapsulating film obtained by encapsulating an electronic device by curing a composition for encapsulating an electronic device containing a photopolymerizable monomer and a photopolymerization initiator,

[0023] contains (meth)acrylate as the photopolymerizable monomer,

[0024] The electronic device encapsulating film has a curing rate of 80% or more, and a residue rate of the electronic device encapsulating film measured by a differential thermal-thermogravimetric analysis (TG-DTA) is 3% or more.

[0025] 9. An electronic device packaging film is an electronic device packaging film for packaging electronic devices, having:

[0026] The first encapsulation layer comprises silicon nitride, silicon oxide or silicon oxynitride, and

[0027] The second encapsulating layer uses the composition for encapsulating an electronic device according to any one of items 1 to 7.

[0028] 10. The electronic device encapsulation film according to item 9, further comprising a third encapsulation layer containing silicon nitride, silicon oxide or silicon oxynitride on the second encapsulation layer.

[0029] 11. A method for forming an electronic device encapsulating film, comprising forming an electronic device encapsulating film using the composition for encapsulating an electronic device according to any one of items 1 to 7, the method comprising:

[0030] A step of forming a first encapsulation layer on the electronic device by a vapor phase method, and

[0031] A step of forming a second encapsulating layer by applying the electronic device encapsulating composition onto the first encapsulating layer.

[0032] 12. The method for forming an electronic device encapsulation film according to item 11, further comprising the step of forming a third encapsulation layer on the second encapsulation layer by a vapor phase method.

[0033] 13. The method for forming an electronic device encapsulation film according to item 11, wherein the second encapsulation layer is formed by an inkjet method.

[0034] According to the above aspect of the present invention, a composition for encapsulating an electronic device that can provide an encapsulating film having good relative dielectric constant stability and adhesion can be provided. In addition, an electronic device encapsulating film using the encapsulating composition and a method for forming the electronic device encapsulating film can be provided.

[0035] The mechanism of effect or action of the present invention is not clear, but is presumed as follows.

[0036] (Stability of relative dielectric constant)

[0037] The relative dielectric constant indicates the ease of polarization when an electric field is applied. It is believed that whether polarization occurs depends on the directionality and ease of migration of the molecules of the components of the encapsulation film after the encapsulation composition is cured. Therefore, it is preferred that the molecules of the components of the encapsulation film are more difficult to migrate, and the less uncured components of the encapsulation film, the better.

[0038] Therefore, in the present invention, it is presumed that the uncured components of the encapsulating film are reduced by setting the curing rate of the encapsulating film to 80% or more, and the molecules are less likely to migrate, so that the relative dielectric constant is stabilized.

[0039] In addition, the molecular structure after curing is well polymerized and cross-linked. Therefore, it is speculated that in the present invention, by making the above-mentioned residue rate more than 3%, a film with a high residue rate is formed, so that the film is polymerized and cross-linked, and the stability of the relative dielectric constant against heat becomes higher.

[0040] (Adhesion)

[0041] For example, when there is a CVD film as the base of the packaging film, when the packaging film is peeled off from the CVD film, it is believed that the peeling is carried out by interface peeling and cohesion peeling. The interface peeling is related to the mechanical properties of the film and the stress of the film. It is believed that the film is appropriately polymerized and cross-linked, so that these mechanical properties are high and the film stress is in an appropriate range, so that the close fit becomes good. In addition, by becoming a fully cured film, the strength of the film itself is also increased, which can inhibit cohesion peeling.

[0042] Therefore, it is speculated that in the present invention, by making the curing rate of the packaging film 80% or more and the above-mentioned residue rate 3% or more, the mechanical properties of the film are improved, the stress of the film is within an appropriate range, the adhesion is good, and the cohesion and peeling can be suppressed because it becomes a fully cured film. DETAILED DESCRIPTION

[0043] The composition for encapsulating electronic devices of the present invention is a composition for encapsulating electronic devices containing a photopolymerizable monomer and a photopolymerization initiator, containing a (meth)acrylate as the photopolymerizable monomer, and the composition is soluble in water at 1.5 Jcm -2When cured by irradiation with ultraviolet rays having a wavelength of 395 nm, the formed electronic device encapsulation film has a curing rate of 80% or more, and a residue rate of 3% or more as measured by a differential thermal-thermogravimetric analysis (TG-DTA) apparatus.

[0044] This feature is a common or corresponding technical feature in the following embodiments.

[0045] As an embodiment of the present invention, in terms of stabilization of the relative dielectric constant and better adhesion, the curing rate is preferably 90% or more.

[0046] In terms of stabilization of the relative dielectric constant and better adhesion, the residue ratio is preferably 5% or more, particularly preferably 10% or more.

[0047] In addition, in order to achieve low dielectric constant and suppress interference between the display element of the electronic device and the touch sensor disposed on the display element, it is preferred to use 1.5 Jcm in a nitrogen environment. -2 The relative dielectric constant of the electronic device encapsulation film formed when cured by irradiation with ultraviolet light of a wavelength of 395 nm is 3.1 or less. This is particularly preferred when using large electronic devices such as notebook computers or touch sensors using active styluses.

[0048] In terms of stability of relative dielectric constant and adhesion, the average number of (meth)acrylic groups of the photopolymerizable monomer contained in the composition for encapsulating electronic components is preferably within a range of 1.3 to 1.5.

[0049] In order to improve the stability of relative dielectric constant, adhesion and curing rate, the methacrylate ratio of the photopolymerizable monomer contained in the composition for encapsulating electronic components is preferably within a range of 50 to 80%.

[0050] An electronic device packaging film in one embodiment of the present invention is an electronic device packaging film that encapsulates electronic devices by curing an electronic device packaging composition containing a photopolymerizable monomer and a photopolymerization initiator, and contains (meth)acrylate as the above-mentioned photopolymerizable monomer. The curing rate of the above-mentioned electronic device packaging film is greater than 80%, and the residue rate of the above-mentioned electronic device packaging film based on a differential thermal-thermogravimetric simultaneous measurement device (TG-DTA) is greater than 3%.

[0051] This makes it possible to produce an electronic device packaging film having excellent stability in relative dielectric constant and adhesion.

[0052] An electronic device encapsulating film according to another embodiment of the present invention is an electronic device encapsulating film for encapsulating an electronic device, and includes a first encapsulating layer containing silicon nitride, silicon oxide, or silicon oxynitride, and a second encapsulating layer using the electronic device encapsulating composition.

[0053] This makes it possible to produce an electronic device packaging film having excellent stability in relative dielectric constant and adhesion.

[0054] In terms of excellent sealing performance, it is preferred that a third sealing layer containing silicon nitride, silicon oxide or silicon oxynitride is provided on the second sealing layer.

[0055] The method for forming an electronic device packaging film of the present invention is a method for forming an electronic device packaging film using the above-mentioned electronic device packaging composition, and the method comprises: a step of forming a first packaging layer on an electronic device using a vapor phase method, and a step of forming a second packaging layer by coating the above-mentioned electronic device packaging composition on the above-mentioned first packaging layer.

[0056] Thus, an electronic device packaging film having excellent relative dielectric constant stability and adhesion can be formed.

[0057] In terms of excellent sealing performance, it is preferable to include a step of forming a third sealing layer on the second sealing layer by a vapor phase method.

[0058] In addition, it is preferable to form the second sealing layer by an inkjet method because the layer can be formed with high precision.

[0059] Hereinafter, the present invention and its constituent elements and forms and modes for carrying out the present invention will be described. It should be noted that in the present application, "to" is used to mean that the numerical values ​​described before and after it are included as the lower limit and the upper limit.

[0060] [Overview of the inkjet electronic device encapsulation composition of the present invention]

[0061] The composition for encapsulating electronic components for inkjet of the present invention (hereinafter, also referred to as "encapsulating composition") is a composition for encapsulating electronic components containing a photopolymerizable monomer and a photopolymerization initiator, containing a (meth)acrylate as the photopolymerizable monomer, and having a molecular weight of 1.5 Jcm -2 When cured by irradiation with ultraviolet rays of a wavelength of 395 nm, the formed electronic device packaging film (hereinafter also referred to as "packaging film") has a curing rate of 80% or more, and the residue rate of the electronic device packaging film based on a differential thermal-thermogravimetric simultaneous measurement device (TG-DTA) is 3% or more.

[0062] <Curing rate>

[0063] The encapsulation composition of the present invention is heated to 1.5 Jcm in a nitrogen environment.-2 The curing rate of the package film formed when cured by irradiation with ultraviolet rays having a wavelength of 395 nm is 80% or more, more preferably 90% or more, and the upper limit is preferably 100%.

[0064] The curing rate can be determined by measuring the FT-IR spectrum of the encapsulating composition before curing and the encapsulating film (cured film) after light irradiation, and the peak (810 cm-1) derived from the C=C bond of the (meth)acryloyl group can be determined. -1 ) is calculated using the following formula.

[0065] Curing rate (%) = (1-a / b) × 100

[0066] a: Peak value derived from C=C bond of the encapsulating composition before curing

[0067] b: Peak from C=C bond of the cured encapsulation film

[0068] As a method for making the curing rate above 80%, for example, there can be mentioned the use of (meth)acrylates that easily undergo free radical reaction, the use of photopolymerization initiators and sensitizers that effectively absorb 395 nm to improve the reaction efficiency, etc. As (meth)acrylates that easily undergo free radical reaction, there can be used (meth)acrylates containing amines, (meth)acrylates having ethylene oxide groups, (meth)acrylates having hydroxyl groups, and (meth)acrylates having 2 or more (meth)acrylate functional groups. In addition, since acrylates are more reactive than methacrylates, compositions with a low methacrylate ratio can be used.

[0069] <Residue rate>

[0070] The encapsulation composition of the present invention has a -2 The residual rate of the package film formed when cured by irradiation with ultraviolet rays having a wavelength of 395 nm is 3% or more, more preferably 5% or more, and particularly preferably 10% or more, as measured by a differential thermal-thermogravimetric analysis (TG-DTA).

[0071] Thermo Plus EVO2 (manufactured by Rigaku Corporation) was used as a differential thermal and thermogravimetric analysis apparatus (TG-DTA). The temperature was raised to 500°C at a heating rate of 10°C / min in a nitrogen atmosphere, and the residue rate was calculated using the following formula: the mass w at 500°C relative to the initial mass w0.

[0072] Residue rate (%) = w / w0 × 100 (%)

[0073] (Residue rate = (1-mass reduction rate) × 100, mass reduction rate = 1-w / w0)

[0074] As a method for making the above-mentioned residue rate 3% or more, for example, the use of (meth)acrylates that are easy to react with free radicals, the use of photopolymerization initiators and sensitizers that effectively absorb 395nm to improve the reaction efficiency, etc. can be cited. In addition, the use of (meth)acrylate structures with high heat resistance can be cited, for example, (meth)acrylates of alicyclic hydrocarbons, (meth)acrylate structures with polybutadiene skeletons can be cited. As acrylate compounds with polybutadiene skeletons, for example, TEAI-1000 and TE-2000 manufactured by Nippon Soda Co., Ltd., BAC-15 and BAC-45 manufactured by Osaka Organic Chemical Industry Co., Ltd., etc. can be cited.

[0075] <Relative dielectric constant>

[0076] The encapsulation composition of the present invention is heated to 1.5 Jcm in a nitrogen environment. -2 The relative dielectric constant of the package film formed when cured by irradiation with ultraviolet rays having a wavelength of 395 nm is preferably 3.1 or less, and more preferably in the range of 2.4 to 2.9.

[0077] The relative dielectric constant can be calculated by the following method using, for example, the capacitance C obtained by an impedance measuring device.

[0078]

[0079] S: The area of ​​the electrode

[0080] d: Electrode spacing

[0081] ε y : Relative dielectric constant of the sample

[0082] ε0: area of ​​true vacuum

[0083] In addition, as a method for making the above relative dielectric constant less than 3.1, for example, the use of a (meth)acrylate structure with low polarizability and dipole moment can be cited. For example, (meth)acrylates with a small number of hydroxyl groups, (meth)acrylates with a small number of heteroatoms, (meth)acrylates with a small number of ester groups, methacrylate (meth)acrylates, (meth)acrylates of alicyclic hydrocarbons, and (meth)acrylates containing fluorine can be cited. In addition, the use of (meth)acrylates with large molecular volumes can be cited, for example, (meth)acrylates with alicyclic hydrocarbons, (meth)acrylates with large molecular weights, and (meth)acrylates with alkylene groups with carbon chains of 8 or more can be cited.

[0084] [Composition of the composition for encapsulating electronic devices]

[0085] The composition for encapsulating electronic components of the present invention contains a photopolymerizable monomer and a photopolymerization initiator.

[0086] As the photopolymerizable monomer, a (meth)acrylate is contained.

[0087] In this specification, "(meth)acrylate" means at least one of acrylate and methacrylate.

[0088] In addition, the "electronic device" in the present invention refers to an element that generates, amplifies, converts or controls electrical signals by using the kinetic energy and potential energy of electrons. Examples include active elements such as light emitting diode elements, organic electroluminescent elements, photoelectric conversion elements and transistors. In addition, in the present invention, passive elements such as resistors and capacitors that passively work by "impeding" or "accumulating" the action of other elements are also included in the electronic device.

[0089] Therefore, the encapsulating composition of the present invention is used to form an encapsulating film for encapsulating the above-mentioned electronic device.

[0090] <Photopolymerizable monomer>

[0091] "Photopolymerizable monomer" refers to a photopolymerizable monomer (also referred to as "photocurable monomer") that can undergo a polymerization (curing) reaction by absorbing light by itself or a photopolymerization initiator and generating active ions or free radicals. As the above-mentioned photopolymerizable monomer, a non-silicon monomer that does not contain silicon (Si) can be used, for example, a monomer composed only of elements selected from C, H, O, N or S, but it is not limited thereto. The photopolymerizable monomer can be synthesized by a conventional synthesis method and used, or it can be purchased as a commercially available product and used.

[0092] As the above-mentioned photopolymerizable monomer, there can be mentioned the following photopolymerizable monomer (A) without an aromatic hydrocarbon group, the photopolymerizable monomer (B) with an aromatic hydrocarbon group, etc. As described above, when making a packaging film, it is appropriately selected from these photopolymerizable monomers in a manner such that the above-mentioned curing rate and residue rate satisfy the above-mentioned range.

[0093] (Average (meth)acrylic acid base number)

[0094] In terms of the stability of relative dielectric constant and adhesion, the average number of (meth)acrylic groups of the photopolymerizable monomer contained in the encapsulating composition of the present invention is preferably within a range of 1.3 to 1.5.

[0095] The average number of (meth)acrylic acid groups can be calculated as follows using the number n of (meth)acrylic acid groups contained in the monomer and the mass ratio w when the total mass of the monomers is taken as 1.

[0096] Average number of (meth)acrylic acid groups = n1×w1+n2×w2+···

[0097] (The subscripts n and w indicate the monomer number.)

[0098] (Methacrylate ratio)

[0099] In order to improve the stability of relative dielectric constant, adhesion and curing rate, the methacrylate ratio of the photopolymerizable monomer contained in the encapsulating composition of the present invention is preferably within a range of 50 to 80%.

[0100] The methacrylate ratio can be calculated as follows using the total mass wm of monomers having a methacrylic group and the total mass wa of monomers having an acrylic group.

[0101] Methacrylate ratio (%) = wm / (wa+wm)×100

[0102] <Photopolymerizable monomer (A) not having an aromatic hydrocarbon group>

[0103] The above-mentioned photopolymerizable monomer (A) not having an aromatic hydrocarbon group (hereinafter also referred to as "photopolymerizable monomer (A)") does not contain an aromatic hydrocarbon group, and may contain a monomer having 1 to 20, specifically 1 to 6, one or more selected from vinyl, acrylic and methacrylic groups as photocurable functional groups (photopolymerizable functional groups), for example, it may contain 1 to 3, 1 to 2, 1 or 2.

[0104] In the present invention, the weight average molecular weight of the photopolymerizable monomer (A) may be in the range of 100 to 500 g / mol, 130 to 400 g / mol, or 200 to 300 g / mol. By keeping the weight average molecular weight of the monomer within the range, a more favorable effect can be exhibited in the process.

[0105] The photopolymerizable monomer (A) may include a monofunctional monomer or a polyfunctional monomer having a photocurable functional group, or a mixture thereof.

[0106] Specifically, the above-mentioned photopolymerizable monomer (A) can be a (meth)acrylate monomer, which can be an unsaturated carboxylic acid ester having an alkyl group with 1 to 20 carbon atoms, a cycloalkyl group with 3 to 20 carbon atoms, a hydroxyl group and an alkyl group with 1 to 20 carbon atoms; an unsaturated carboxylic acid ester having an aminoalkyl group with 1 to 20 carbon atoms; a vinyl ester of a saturated or unsaturated carboxylic acid with 1 to 20 carbon atoms; a cyanide vinyl compound; an unsaturated amide compound; a monofunctional or polyfunctional (meth)acrylate of a monohydric alcohol or a polyhydric alcohol, etc.

[0107] The above-mentioned "polyol" is an alcohol having two or more hydroxyl groups, and can refer to an alcohol having 2 to 20, preferably 2 to 10, more preferably 2 to 6 hydroxyl groups.

[0108] In one example, the (meth)acrylate monomer having no aromatic hydrocarbon group in the photopolymerizable monomer (A) may be a mono(meth)acrylate, a di(meth)acrylate, a tri(meth)acrylate, a tetra(meth)acrylate, or the like having a substituted or unsubstituted C1-C20 (carbon number 1-20) alkyl group, a substituted or unsubstituted C1-C20 alkylsilyl group, a substituted or unsubstituted C3-C20 cycloalkyl group, a substituted or unsubstituted C1-C20 alkylene group, an amine group, an oxyethylene group, or the like.

[0109] Specifically, the (meth)acrylate monomers without an aromatic hydrocarbon group may include: unsaturated carboxylic acid esters of (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, and cyclohexyl (meth)acrylate; unsaturated carboxylic acid aminoalkyl esters such as 2-aminoethyl (meth)acrylate and 2-dimethylaminoethyl (meth)acrylate; saturated or unsaturated carboxylic acid vinyl esters such as vinyl acetate; cyanide vinyl compounds such as (meth)acrylonitrile; unsaturated amide compounds such as (meth)acrylamide; ethylene glycol di(meth)acrylate )acrylate, triethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, octanediol di(meth)acrylate, nonanediol di(meth)acrylate, decanediol di(meth)acrylate, undecanediol di(meth)acrylate, dodecanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol di(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate or a mixture thereof, but is not limited thereto.

[0110] In one example of the present invention, the photopolymerizable monomer (A) may be a non-aromatic monomer containing no aromatic group and may include at least any one of a mono(meth)acrylate having an alkyl group having 1 to 20 carbon atoms, a mono(meth)acrylate having an amine group, a di(meth)acrylate having a substituted or unsubstituted alkylene group having 1 to 20 carbon atoms, a di(meth)acrylate having an oxyethylene group, a tri(meth)acrylate having an oxyethylene group, a mono(meth)acrylate having a cyclic hydrocarbon alkyl group, and a di(meth)acrylate.

[0111] The mono(meth)acrylate having a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms may specifically be decyl(meth)acrylate, undecyl(meth)acrylate, lauryl(meth)acrylate, tridecyl(meth)acrylate, tetradecyl(meth)acrylate, pentadecyl(meth)acrylate, hexadecyl(meth)acrylate, heptadecyl(meth)acrylate, octadecyl(meth)acrylate, nonadecyl(meth)acrylate, eicosyl(meth)acrylate or a mixture thereof, but is not limited thereto.

[0112] The mono(meth)acrylate having an amine group may be 2-aminoethyl(meth)acrylate, 2-dimethylaminoethyl(meth)acrylate, or a mixture thereof, but is not limited thereto.

[0113] The di(meth)acrylate having a substituted or unsubstituted alkylene group having 1 to 20 carbon atoms may be, for example, a di(meth)acrylate having an alkylene group having 1 to 20 carbon atoms, or a non-silicon-based di(meth)acrylate containing a substituted or unsubstituted long-chain alkylene group.

[0114] The di(meth)acrylate having a substituted or unsubstituted alkylene group having 1 to 20 carbon atoms may be, for example, octanediol di(meth)acrylate, nonanediol di(meth)acrylate, decanediol di(meth)acrylate, undecanediol di(meth)acrylate, dodecanediol di(meth)acrylate or a mixture thereof, but is not limited thereto.

[0115] When the (meth)acrylate having a substituted or unsubstituted alkylene group having 1 to 20 carbon atoms is contained, the photocuring rate of the encapsulating composition of the present invention is further improved, and the viscosity can be reduced.

[0116] The di(meth)acrylate or tri(meth)acrylate having an oxyethylene group may specifically be ethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, or a mixture thereof, but is not limited thereto.

[0117] The mono(meth)acrylate and di(meth)acrylate having a cyclic hydrocarbon alkyl group may specifically be isobornyl(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, dicyclopentanyl(meth)acrylate, dicyclopentenyloxyethyl(meth)acrylate, and dicyclopentenyl(meth)acrylate, but are not limited thereto.

[0118] The photopolymerizable monomer (A) is preferably contained in an amount of 55 to 95% by mass, more preferably 60 to 90% by mass, relative to the total mass of the photopolymerizable monomers (photopolymerizable monomer (A) and photopolymerizable monomer (B)). By being within the above range, the viscosity of the encapsulating composition of the present invention is suitable for forming an encapsulating film for electronic devices.

[0119] <Photopolymerizable monomer (B) having an aromatic hydrocarbon group>

[0120] The above-mentioned photopolymerizable monomer (B) having an aromatic hydrocarbon group (hereinafter also referred to as "photopolymerizable monomer (B)") has a structure represented by the following general formula (1) and contains two or more phenyl groups and hetero atoms, and the above-mentioned photopolymerizable monomer (B) contains at least mono(meth)acrylate or di(meth)acrylate.

[0121] General formula (1)

[0122]

[0123] [In the above general formula (1), P represents a hydrocarbon group containing two or more substituted or unsubstituted phenyl groups, or a heteroatom-containing hydrocarbon group containing two or more substituted or unsubstituted phenyl groups. 1 and Z 2 Each independently has a structure represented by the following general formula (2). a and b are each an integer of 0 to 2, and a+b is an integer of 1 to 4.]

[0124] General formula (2)

[0125]

[0126] [In the above general formula (2), * is a linking portion to the carbon of P. X represents a single bond, O or S. Y represents a substituted or unsubstituted linear alkylene group having 1 to 10 carbon atoms, or a substituted or unsubstituted alkoxy group having 1 to 20 carbon atoms. R 1 represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms. c is an integer of 0 or 1.]

[0127] In the above general formula (1), P represents a hydrocarbon group containing two or more substituted or unsubstituted phenyl groups, or a heteroatom-containing hydrocarbon group containing two or more substituted or unsubstituted phenyl groups.

[0128] The above-mentioned hydrocarbon group containing two or more substituted or unsubstituted phenyl groups, or the heteroatom-containing hydrocarbon group containing two or more substituted or unsubstituted phenyl groups refers to a group in which two or more substituted or unsubstituted phenyl groups are not condensed and are connected by a single bond, an oxygen atom, a sulfur atom, a substituted or unsubstituted alkyl group having 1 to 5 carbon atoms, a heteroatom-substituted or unsubstituted alkylene group having 3 to 6 carbon atoms, a vinylene group, an ethynylene group or a carbonyl group.

[0129] For example, the hydrocarbon group containing two or more phenyl groups or the heteroatom-containing hydrocarbon group containing two or more phenyl groups may include a substituted or unsubstituted biphenyl group, a substituted or unsubstituted triphenylmethyl group, a substituted or unsubstituted terphenyl group, a substituted or unsubstituted biphenylene group, a substituted or unsubstituted terphenylene group, a substituted or unsubstituted quaterphenylene group, a substituted or unsubstituted 2-phenyl-2-(phenylthio)ethyl group, a substituted or unsubstituted 2,2-diphenylpropyl group, a substituted or unsubstituted diphenylmethyl group, a substituted or unsubstituted cumylphenyl group, a substituted or unsubstituted bisphenol F group, a substituted or unsubstituted bisphenol A group, a substituted or unsubstituted biphenyloxy group, a substituted or unsubstituted terphenyloxy group, a substituted or unsubstituted quaterphenyloxy group, a substituted or unsubstituted pentphenyloxy group, and structural isomers thereof, but are not limited thereto.

[0130] The monomer having two or more substituted or unsubstituted phenyl groups may be a mono(meth)acrylate, a di(meth)acrylate or a mixture thereof, and examples thereof include 4-(meth)acryloyloxy-2-hydroxybenzophenone, 3,3-diphenylethyl(meth)acrylate, benzoyloxyphenyl(meth)acrylate, bisphenol A di(meth)acrylate, ethoxylated bisphenol A di(meth)acrylate, bisphenol F di(meth)acrylate, ethoxylated bisphenol F di(meth)acrylate, 4-cumylphenoxyethyl acrylate, ethoxylated bisphenylfluorene diacrylate, 2-phenylphenoxyethyl(meth)acrylate, 2,2'-phenylphenoxyethyl di(meth)acrylate, 2-phenylphenoxypropyl(meth)acrylate, 2,2'-phenylphenoxypropyldi(meth)acrylate, 2-phenylphenoxybutyl(meth)acrylate, 2,2'-phenylphenoxybutyldi(meth)acrylate, 2-( 2-(3-phenylphenyl)ethyl (meth)acrylate, 2-(4-benzylphenyl)ethyl (meth)acrylate, 2-phenyl-2-(phenylthio)ethyl (meth)acrylate, 2-(triphenylmethoxy)ethyl (meth)acrylate, 4-(triphenylmethoxy)butyl (meth)acrylate, 3-(biphenyl-2-yloxy)butyl (meth)acrylate, 2-(biphenyl-2-yloxy)butyl (meth)acrylate, 4-(biphenyl-2-yloxy)propyl (meth)acrylate, acrylate, 3-(biphenyl-2-yloxy)propyl (meth)acrylate, 2-(biphenyl-2-yloxy)propyl (meth)acrylate, 4-(biphenyl-2-yloxy)ethyl (meth)acrylate, 3-(biphenyl-2-yloxy)ethyl (meth)acrylate, 2-(4-benzylphenyl)ethyl (meth)acrylate, 4,4'-bis(acryloyloxymethyl)biphenyl, 2,2'-bis(2-acryloyloxyethoxy)biphenyl, structural isomers thereof, or mixtures thereof, but are not limited thereto.

[0131] In addition, the (meth)acrylate mentioned in the present invention is just an example, and the present invention is not limited to this.

[0132] In addition, the present invention includes all acrylates in a structural isomer relationship. For example, even if only 2,2'-phenylphenoxyethyl di(meth)acrylate is mentioned as an example of the present invention, the present invention also includes all 3,2'-phenylphenoxyethyl di(meth)acrylate, 3,3'-phenylphenoxyethyl di(meth)acrylate, etc. corresponding to the structural isomer.

[0133] In one example of the present invention, the monomer having two or more phenyl groups may be a mono(meth)acrylate represented by the following general formula (4).

[0134] General formula (4)

[0135]

[0136] In the above general formula (4), R 2 is hydrogen or methyl, R 3 is a substituted or unsubstituted linear alkylene group having 1 to 10 carbon atoms, or a substituted or unsubstituted alkoxy group having 1 to 20 carbon atoms, R 4 It is a hydrocarbon group containing two or more substituted or unsubstituted phenyl groups, or a heteroatom-containing hydrocarbon group containing two or more substituted or unsubstituted phenyl groups.

[0137] For example, the above-mentioned hydrocarbon group containing two or more substituted or unsubstituted phenyl groups, or the heteroatom-containing hydrocarbon group containing two or more substituted or unsubstituted phenyl groups refers to a group in which two or more substituted or unsubstituted phenyl groups are not condensed and are connected by a single bond, an oxygen atom, a sulfur atom, a substituted or unsubstituted alkyl group having 1 to 3 carbon atoms, a heteroatom-substituted or unsubstituted alkylene group having 3 to 6 carbon atoms, a vinylene group, an ethynylene group or a carbonyl group.

[0138] For example, the above-mentioned hydrocarbon group containing two or more substituted or unsubstituted phenyl groups, or the heteroatom-containing hydrocarbon group containing two or more substituted or unsubstituted phenyl groups may include a substituted or unsubstituted biphenyl group, a substituted or unsubstituted triphenylmethyl group, a substituted or unsubstituted terphenyl group, a substituted or unsubstituted biphenylene group, a substituted or unsubstituted terphenylene group, a substituted or unsubstituted quaterphenylene group, a substituted or unsubstituted 2-phenyl-2-(phenylthio)ethyl group, a substituted or unsubstituted 2,2-diphenylpropyl group, a substituted or unsubstituted diphenylmethyl group, a substituted or unsubstituted cumylphenyl group, a substituted or unsubstituted bisphenol F group, a substituted or unsubstituted bisphenol A group, a substituted or unsubstituted biphenyloxy group, a substituted or unsubstituted terphenyloxy group, a substituted or unsubstituted quaterphenyloxy group, a substituted or unsubstituted pentphenyloxy group, etc., but are not limited thereto.

[0139] In one example of the present invention, the monomer having two or more phenyl groups may be a di(meth)acrylate represented by the following general formula (5).

[0140] General formula (5)

[0141]

[0142] In the above general formula (5), R 5 , R 9 are each independently hydrogen or methyl, R 6 , R 8 are each independently a substituted or unsubstituted linear alkylene group having 1 to 10 carbon atoms, or a substituted or unsubstituted alkoxy group having 1 to 20 carbon atoms, 7 It is a hydrocarbon group containing two or more substituted or unsubstituted phenyl groups, or a heteroatom-containing hydrocarbon group containing two or more substituted or unsubstituted phenyl groups.

[0143] For example, the above-mentioned hydrocarbon group containing two or more substituted or unsubstituted phenyl groups, or the heteroatom-containing hydrocarbon group containing two or more substituted or unsubstituted phenyl groups refers to a group in which two or more substituted or unsubstituted phenyl groups are not condensed and are connected by a single bond, an oxygen atom, a sulfur atom, a substituted or unsubstituted alkyl group having 1 to 4 carbon atoms, a heteroatom-substituted or unsubstituted alkylene group having 3 to 6 carbon atoms, a vinylene group, an ethynylene group or a carbonyl group.

[0144] For example, the hydrocarbon group may include substituted or unsubstituted biphenylene, substituted or unsubstituted triphenylmethylene, substituted or unsubstituted terphenylene, substituted or unsubstituted quaterphenylene, 2-phenyl-2-(phenylthio)ethylene, 2,2-diphenylpropylene, diphenylmethylene, etc., but is not limited thereto.

[0145] In the above general formula (1), a and b are integers of 0 to 2 respectively, and a+b is an integer of 1 to 4. In one example, a+b is an integer of 1 or 2.

[0146] The weight average molecular weight of the monomer having two or more substituted or unsubstituted phenyl groups is preferably in the range of 100 to 1000 g / mol, more preferably in the range of 130 to 700 g / mol, and particularly preferably in the range of 150 to 600 g / mol.

[0147] When the content is within the above range, a packaging film having a higher transmittance can be provided.

[0148] The photopolymerizable monomer (B) having an aromatic hydrocarbon group is preferably contained in an amount of 5 to 45% by mass, more preferably 10 to 40% by mass, relative to the total mass of the photopolymerizable monomers (photopolymerizable monomer (A) and photopolymerizable monomer (B)). By being within the above range, the viscosity is suitable for forming a packaging film.

[0149] In addition, specific examples of the photopolymerizable monomers (A) and (B) include the monomers listed in the examples described below in addition to the above monomers. Preferred combinations of the photopolymerizable monomers in the present invention are described in the examples described below.

[0150] <Photopolymerization initiator>

[0151] The photopolymerization initiator is not particularly limited as long as it is a common photopolymerization initiator capable of undergoing a photocurable reaction.

[0152] As the photopolymerization initiator, for example, a triazine-based, acetophenone-based, benzophenone-based, thioxanthone-based, benzoin-based, phosphorus-based, oxime-based, or a mixture thereof may be included.

[0153] The triazine initiator can be 2,4,6-trichloro-s-triazine, 2-phenyl-4,6-bis(trichloromethyl)-s-triazine, 2-(3',4'-dimethoxyphenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4'-methoxynaphthyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-methoxyphenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-tolyl)-4,6-bis(trichloromethyl)-s-triazine, s-triazine, 2-biphenyl-4,6-bis(trichloromethyl)-s-triazine, bis(trichloromethyl)-6-phenylvinyl-s-triazine, 2-(naphthalene-1-yl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4-methoxynaphthalene-1-yl)-4,6-bis(trichloromethyl)-s-triazine, 2,4-trichloromethyl(piperonyl)-6-triazine, 2,4-(trichloromethyl(4'-methoxyphenylvinyl)-6-triazine or a mixture thereof.

[0154] The acetophenone-based initiator may be 2,2'-diethoxyacetophenone, 2,2'-dibutoxyacetophenone, 2-hydroxy-2-methylpropiophenone, p-tert-butyltrichloroacetophenone, p-tert-butyldichloroacetophenone, 4-chloroacetophenone, 2,2'-dichloro-4-phenoxyacetophenone, 2-methyl-1-(4-(methylthio)phenyl)-2-morpholinopropane-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butane-1-one, and mixtures thereof.

[0155] The benzophenone-based initiator may be benzophenone, benzoylbenzoic acid, methyl benzoylbenzoate, 4-phenylbenzophenone, hydroxybenzophenone, acrylated benzophenone, 4,4'-bis(dimethylamino)benzophenone, 4,4'-dichlorobenzophenone, 3,3'-dimethyl-2-methoxybenzophenone or a mixture thereof.

[0156] The thioxanthone-based initiator may be thioxanthone, 2-methylthioxanthone, isopropylthioxanthone, 2,4-diethylthioxanthone, 2,4-diisopropylthioxanthone, 2-chlorothioxanthone or a mixture thereof.

[0157] The benzoin-based initiator may be benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, benzil dimethyl ketal or a mixture thereof.

[0158] The phosphorus-based initiator may be bisbenzoylphenylphosphine oxide, benzoyldiphenylphosphine oxide or a mixture thereof.

[0159] The oxime may be 2-(o-benzoyloxime)-1-[4-(phenylthio)phenyl]-1,2-octanedione and 1-(o-acetoxime)-1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone, or a mixture thereof.

[0160] The photopolymerization initiator is preferably contained in the encapsulation composition of the present invention in an amount of about 0.1 to 20 parts by mass relative to 100 parts by mass of the total of the photopolymerizable monomer and the photopolymerization initiator. By being within the above range, photopolymerization can be fully carried out during exposure, and a decrease in transmittance due to residual unreacted initiator after photopolymerization can be prevented.

[0161] Specifically, the photopolymerization initiator is preferably contained in an amount within a range of 0.5 to 10 parts by mass, more specifically 1 to 5 parts by mass.

[0162] In addition, the photopolymerization initiator is preferably contained in the encapsulating composition of the present invention in an amount of 0.1 to 10% by mass, more preferably 0.1 to 5% by mass, based on the solid content. By being within the above range, photopolymerization can be sufficiently carried out and a decrease in transmittance due to residual unreacted initiator can be prevented.

[0163] In addition, carbazole-based, diketone-based, sulfonium-based, iodine-based Instead of the above-mentioned photopolymerization initiator, a photoacid generator or a photopolymerization initiator such as a photoacid generator, a diazo generator, or a biimidazole generator can be used.

[0164] <Other additives>

[0165] The encapsulation composition of the present invention may further contain other components including antioxidants, heat stabilizers, photosensitizers, dispersants, thermal crosslinking agents and surfactants within the range of obtaining the effects of the present invention. These components may be contained in the encapsulation composition of the present invention alone or in two or more combinations.

[0166] The above antioxidant can improve the thermal stability of the encapsulation layer. The antioxidant may include one or more selected from phenol, quinone, amine and phosphite, but is not limited thereto. For example, as an antioxidant, tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate)]methane, tris(2,4-di-tert-butylphenyl)phosphite, etc. may be cited.

[0167] The antioxidant is preferably contained in the encapsulating composition in an amount of 0.01 to 3 parts by mass, more preferably 0.01 to 1 part by mass, based on 100 parts by mass of the total of the photopolymerizable monomer and the photopolymerization initiator. Within the above range, excellent thermal stability can be exhibited.

[0168] The heat stabilizer is contained in the encapsulating composition to suppress a change in viscosity of the encapsulating composition at room temperature, and a common heat stabilizer can be used without limitation.

[0169] For example, as the heat stabilizer, a sterically hindered phenolic heat stabilizer can be used, specifically, poly(dicyclopentadiene-co-p-cresol), octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 2,6-di-tert-butyl-4-methylphenol, 2,2'-methylene-bis(4-methyl-6-tert-butylphenol), 6,6'-di-tert-butyl-2,2'-thiodi-p-cresol, tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl) isocyanurate, triethylene glycol-bis(3-tert-butyl-4-hydroxy-5-methylphenyl), 4,4'-thiobis(6-tert-butyl-m-cresol), 3,3' The invention may be selected from the group consisting of: -bis(3,5-di-tert-butyl-4-hydroxyphenyl)-N,N'-hexamethylenebispropionamide, pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), stearyl-3,5-di-tert-butyl-4-hydroxyphenylpropionate, pentaerythritol tetrakis-1,3,5-tris(2,6-dimethyl-3-hydroxy-4-tert-butylbenzyl)isocyanurate, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, 1,3,5-tris(2-hydroxyethyl)isocyanurate-tris(3,5-di-tert-butylhydroxyphenylpropionate), but is not limited thereto.

[0170] The thermal stabilizer is contained in the encapsulating composition in an amount of 2000 ppm or less, preferably in a range of 0.01 to 2000 ppm, and more preferably in a range of 100 to 1000 ppm, based on the solid content relative to the total of the photopolymerizable monomer and the photopolymerization initiator. By being within the above range, the thermal stabilizer can further improve the storage stability and processability of the encapsulating composition in a liquid state.

[0171] The photosensitizer is a compound that has a function of transferring absorbed light energy to a photopolymerization initiator, and therefore can have the original photopolymerization initiator function even if the photopolymerization initiator used does not have absorption corresponding to light from a light source.

[0172] Examples of the photosensitizer include anthracene derivatives such as 9,10-dibutoxyanthracene; benzoin derivatives such as benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether;

[0173] Benzophenone derivatives such as benzoylbenzoic acid methyl ester, 4-phenylbenzophenone, 4-benzoyl-4'-methyl-diphenyl sulfide, 3,3',4,4'-tetrakis(tert-butylperoxycarbonyl)benzophenone, 2,4,6-trimethylbenzophenone, 4-benzoyl-N,N-dimethyl-N-[2-(1-oxo-2-propyleneoxy)ethyl]benzyl ammonium bromide, and (4-benzoylbenzyl)trimethylammonium chloride;

[0174] Thioxanthone derivatives such as 2-isopropylthioxanthone, 4-isopropylthioxanthone, 2,4-diethylthioxanthone, 2,4-dichlorothioxanthone, 1-chloro-4-propoxythioxanthone, and 2-(3-dimethylamino-2-hydroxy)-3,4-dimethyl-9H-thioxanthone-9-one meta-chloride; and other compounds. Among them, anthracene derivatives, benzoin derivatives, benzophenone derivatives, anthraquinone derivatives, and thioxanthone derivatives are preferably used.

[0175] <Ultraviolet curing>

[0176] As the ultraviolet rays irradiated to cure the encapsulating composition of the present invention, a known method can be used, and there is no particular limitation as long as the ultraviolet rays are irradiated in the range of 200 to 400 nm to cure. From the viewpoint of preventing degradation of electronic devices, it is preferred to use a 395 nm LED.

[0177] As long as the encapsulation composition is cured in an environment where ultraviolet rays are irradiated, a known method can be used, and there is no particular limitation as long as the curing is performed by irradiating ultraviolet rays. From the viewpoint of preventing degradation of electronic devices and preventing the influence of curing inhibition caused by oxygen, it is preferably irradiated in an inert gas environment. It is particularly preferred to irradiate under a nitrogen or argon atmosphere.

[0178] <Physical Properties>

[0179] From the viewpoint of further improving the ejection property from an inkjet head, the viscosity of the encapsulating composition of the present invention is preferably in the range of 3 to 30 mPa·s. From the viewpoint of further improving the ejection property from an inkjet head, the surface tension is preferably 15 mN / m or more and less than 45 mN / m.

[0180] The viscosity of the encapsulating composition of the present invention can be determined, for example, by measuring the temperature change of the dynamic viscoelasticity of the encapsulating composition using various rheometers.

[0181] In the present invention, these viscosities are values ​​obtained by the following method. The encapsulation composition of the present invention is placed in a stress-controlled rheometer Physica MCR300 (diameter of vertebral plate: 75 mm, cone angle: 1.0°, manufactured by Anton Paar). Next, the encapsulation composition is heated to 100°C, and the encapsulation composition is cooled to 20°C under the conditions of a cooling rate of 0.1°C / s, a strain of 5%, and an angular frequency of 10 radian / s to obtain a temperature change curve of dynamic viscoelasticity.

[0182] The encapsulating composition of the present invention may contain pigment particles. When the encapsulating composition of the present invention contains a pigment, the average particle size of the pigment particles is within the range of 0.08 to 0.5 μm, and the maximum particle size is preferably within the range of 0.3 to 10 μm, from the viewpoint of further improving the ejection property from an inkjet head.

[0183] The average particle size of the pigment particles in the present invention refers to the value obtained by the dynamic light scattering method using a Zetasizer Nano ZSP manufactured by Malvern. It should be noted that the concentration of the encapsulating composition containing the coloring material is high and light is not transmitted in the measuring instrument, so the encapsulating composition is diluted 200 times before measurement. The measurement temperature is room temperature (25°C).

[0184] In addition, for the encapsulating composition of the present invention, from the perspective of inkjet ejection properties and droplet stabilization during ink flight, the Ohnesorg number (Oh) represented by the following formula 1, which is composed of its density ρ, the surface tension σ of the above-mentioned encapsulating composition, the viscosity μ of the above-mentioned encapsulating composition, and the nozzle diameter D0, is preferably in the range of 0.1 to 1.

[0185]

[0186] The encapsulation composition of the present invention is preferably prepared to provide a cured polymer having a Tg (glass transition temperature) of 80° C. or higher in the film after polymerization. From the viewpoint of ensuring stability in the formation process, driving temperature, and reliability test of electronic devices, the Tg of the film after polymerization is preferably 80° C. or higher.

[0187] [Method for forming an electronic device packaging film]

[0188] The method for forming an electronic device packaging film of the present invention is a method for forming a packaging film using the above-mentioned electronic device packaging composition of the present invention, and the method comprises: a step of forming a first packaging layer on an electronic device using a vapor phase method, and a step of forming a second packaging layer by coating the above-mentioned electronic device packaging composition on the above-mentioned first packaging layer.

[0189] In order to further improve the sealing performance of the electronic device, it is preferable to include a step of forming a third sealing layer on the second sealing layer by a vapor phase method.

[0190] <First sealing layer forming step>

[0191] The first encapsulation layer forming step forms a first encapsulation layer on the electronic device by a vapor phase method.

[0192] As gas phase methods, sputtering methods (for example, reactive sputtering methods including magnetron cathode sputtering, planar magnetron sputtering, dipole AC planar magnetron sputtering, dipole AC rotating magnetron sputtering, etc.), evaporation methods (for example, resistance heating evaporation, electron beam evaporation, ion beam evaporation, plasma assisted evaporation, etc.), thermal CVD method, catalytic chemical vapor deposition method (Cat-CVD), capacitive coupled plasma CVD method (CCP-CVD), optical CVD method, plasma CVD method (PECVD), epitaxial growth method, atomic layer deposition method (ALD) and other chemical evaporation methods can be cited. Among them, formation by ALD method and CVD method is preferred.

[0193] The first encapsulation layer contains silicon nitride (SiNx), silicon nitride oxide (SiNOx), or silicon oxide (SiOx).

[0194] As a specific example of forming the first encapsulation layer, there is a method in which the pressure in the chamber is reduced in advance, and silane (SiH 4 ), ammonia (NH 3 ), and hydrogen (H 2 ) are heated as raw material gases and then supplied into the chamber.

[0195] The thickness of the first encapsulation layer is, for example, preferably in the range of 10 to 1000 nm, more preferably in the range of 100 to 500 nm.

[0196] <Second Encapsulation Layer Formation Step>

[0197] The second encapsulating layer forming step forms the second encapsulating layer by applying the encapsulating composition of the present invention onto the first encapsulating layer.

[0198] Specifically, the method may include a step of coating the encapsulating composition on the first encapsulating layer (coating step), and subjecting the obtained coating film to a modification treatment by irradiating it with vacuum ultraviolet rays in a nitrogen atmosphere.

[0199] (Coating process)

[0200] As a coating method for the encapsulation composition, any appropriate method can be adopted, for example, spin coating, roll coating, flow coating, inkjet, spray coating, printing, dip coating, cast film forming, rod coating, gravure printing, etc. Among them, the inkjet method is preferably used in that the fine patterning required for encapsulating electronic devices such as organic EL elements can be performed as needed.

[0201] As the inkjet method, a known method can be used.

[0202] The inkjet method is roughly divided into two types: the drop-on-demand method and the continuous method, and either method can be used. As the drop-on-demand method, there are electro-mechanical conversion methods (such as single-chamber type, dual-chamber type, curved type, piston type, shared module type, shared wall type, etc.), electro-thermal conversion methods (such as thermal inkjet type, BUBBLEJET (registered trademark) type, etc.), electrostatic attraction methods (such as electric field control type, slit jet type, etc.) and discharge methods (such as electric spark jet type, etc.). From the perspective of the cost and productivity of the inkjet head, it is preferred to use an inkjet head using an electro-mechanical conversion method or an electro-thermal conversion method. It should be noted that the method of dripping droplets (such as coating liquid) according to the inkjet method is sometimes called an "inkjet method".

[0203] The encapsulating composition is preferably applied under a nitrogen atmosphere.

[0204] (Modification process)

[0205] The modification step may include a step of irradiating the obtained coating film with vacuum ultraviolet rays in a nitrogen atmosphere to perform modification treatment after the coating step.

[0206] The modification treatment refers to a conversion reaction of polysilazane into silicon oxide or silicon oxynitride. The modification treatment is also performed in a nitrogen atmosphere and under reduced pressure in a glove box.

[0207] The modification treatment in the present invention can be selected from a known method based on the conversion reaction of polysilazane. In the present invention, it is preferred to use a conversion reaction of plasma, ozone, or ultraviolet light that can perform the conversion reaction at low temperature. Plasma and ozone can use a conventionally known method. In the present invention, it is preferred to form the second encapsulation layer of the present invention by providing the above-mentioned coating film and irradiating vacuum ultraviolet light (also referred to as VUV) with a wavelength of less than 200nm for modification treatment.

[0208] The thickness of the second encapsulating layer is preferably in the range of 0.5 to 20 μm, more preferably in the range of 3 to 10 μm.

[0209] The second encapsulating layer may be a layer whose entire layer is modified, but the thickness of the modified layer after the modification treatment is preferably in the range of 1 to 50 nm, and more preferably in the range of 1 to 30 nm.

[0210] In the step of irradiating the coating film with vacuum ultraviolet rays for modification, the illuminance of the vacuum ultraviolet rays on the coating film surface is preferably 30 to 200 mW / cm 2 The range of 50 to 160 mW / cm 2 By making the illuminance of vacuum ultraviolet light 30mW / cm 2 Above, the modification efficiency can be fully improved, at 200mW / cm 2 When the ratio is less than 0.1, the occurrence rate of damage to the coating film can be extremely suppressed, and damage to the substrate can also be reduced, which is preferred.

[0211] The irradiation energy of vacuum ultraviolet rays on the coating film surface is preferably 1 to 10 J / cm 2 In the range of 3 to 7 J / cm2, from the viewpoint of barrier property and moisture heat resistance for maintaining the drying function, the 2 within the range.

[0212] It should be noted that as the light source of vacuum ultraviolet light, a rare gas excimer lamp is preferably used. Since the efficiency of vacuum ultraviolet light in the vacuum ultraviolet light irradiation process is easily reduced due to the absorption of oxygen, the irradiation of vacuum ultraviolet light is preferably carried out under a state of low oxygen concentration as much as possible. That is, the oxygen concentration during vacuum ultraviolet light irradiation is preferably in the range of 10 to 10000ppm, more preferably in the range of 50 to 5000ppm, further preferably in the range of 80 to 4500ppm, and most preferably in the range of 100 to 1000ppm.

[0213] The modification treatment may also be combined with the heat treatment. By using the heat treatment preferably at a temperature in the range of 50 to 300° C., more preferably in the range of 60 to 150° C., for preferably 1 second to 60 minutes, more preferably 10 seconds to 10 minutes as the heating condition, the dehydration condensation reaction during the modification can be promoted, and the modified body can be formed more effectively.

[0214] As the heat treatment, for example, there are no particular limitations on the method of heating the coating film by contacting the substrate with a heating element such as a heating block, heating the environment with an external heater such as a resistance wire, or using infrared light such as an IR heater. In addition, a method that can maintain the smoothness of the coating film containing the silicon compound can be appropriately selected.

[0215] <Third Encapsulation Layer Formation Step>

[0216] The third encapsulation layer forming step forms a third encapsulation layer on the second encapsulation layer by a vapor phase method.

[0217] As the gas phase method, similar to the gas phase method used in the first encapsulation layer forming step, there can be mentioned a sputtering method (for example, reactive sputtering methods including magnetron cathode sputtering, planar magnetron sputtering, dipole AC planar magnetron sputtering, dipole AC rotating magnetron sputtering, etc.), a vapor deposition method (for example, resistance heating vapor deposition, electron beam vapor deposition, ion beam vapor deposition, plasma assisted vapor deposition, etc.), a thermal CVD method, a catalytic chemical vapor deposition method (Cat-CVD), a capacitively coupled plasma CVD method (CCP-CVD), a photo CVD method, a plasma CVD method (PE-CVD), an epitaxial growth method, a chemical vapor deposition method such as an atomic layer deposition method (ALD), etc. Among them, formation by an ALD method or a CVD method is preferred.

[0218] The third encapsulation layer contains silicon nitride (SiNx), silicon nitride oxide (SiNOx), or silicon oxide (SiOx).

[0219] As a specific example of forming the third encapsulation layer, the following method can be cited: the pressure in the chamber is reduced in advance, and silane (SiH4), ammonia (NH3), and hydrogen (H2) are heated as raw material gases and then supplied into the chamber to form the third encapsulation layer.

[0220] The thickness of the third encapsulation layer is, for example, preferably in the range of 10 to 1000 nm, more preferably in the range of 100 to 500 nm.

[0221] It should be noted that after the package film is formed as described above, a conductive film for a touch sensor may be further formed.

[0222] The conductive film may be composed of a graphene film having excellent flexibility, a metal nanowire film (e.g., a film containing silver nanowires or copper nanowires), or a metal nanoparticle film (e.g., a film containing silver nanoparticles or copper nanoparticles), in addition to a metal compound film such as ITO (Indium Tin Oxide) or IZO (Indium Zinc Oxide). In addition, the conductive film may be composed of a laminated film of multiple metals such as Al film / Ti film / Al film.

[0223] [Electronic device packaging film]

[0224] An electronic device packaging film in one embodiment of the present invention is an electronic device packaging film that encapsulates electronic devices by curing an electronic device packaging composition containing a photopolymerizable monomer and a photopolymerization initiator, and contains (meth)acrylate as the above-mentioned photopolymerizable monomer. The curing rate of the above-mentioned electronic device packaging film is greater than 80%, and the residue rate of the above-mentioned electronic device packaging film based on a differential thermal-thermogravimetric simultaneous measurement device (TG-DTA) is greater than 3%.

[0225] Another embodiment of the electronic device encapsulating film of the present invention is an electronic device encapsulating film for encapsulating an electronic device, comprising a first encapsulating layer containing silicon nitride, silicon oxide or silicon oxynitride, and a second encapsulating layer using the electronic device encapsulating composition of the present invention.

[0226] Such an electronic device encapsulating film of the present invention is formed by the above-mentioned method for forming an electronic device encapsulating film. That is, the second encapsulating layer is formed using the above-mentioned composition for encapsulating an electronic device of the present invention.

[0227] The curing rate of the second encapsulating layer is 80% or more, and the residue rate of the second encapsulating layer measured by differential thermal-thermogravimetric analysis (TG-DTA) is 3% or more.

[0228] In addition, the electronic device encapsulating film of the present invention preferably further comprises a third encapsulating layer containing silicon nitride, silicon oxide or silicon oxynitride on the second encapsulating layer.

[0229] <1st packaging layer>

[0230] The first encapsulation layer is a layer formed on the electronic device by the above-mentioned vapor phase method, and specifically contains silicon nitride, silicon oxide (silicon monoxide, silicon dioxide, etc.), or silicon oxynitride.

[0231] <Second Encapsulation Layer>

[0232] The second encapsulating layer is provided adjacent to the first encapsulating layer, and is formed by applying the encapsulating composition onto the first encapsulating layer.

[0233] Therefore, the second encapsulating layer contains a polymer composed of the specific photopolymerizable monomer contained in the encapsulating composition.

[0234] As a method for detecting that the second encapsulation layer contains the polymer, various conventionally known analytical methods can be used, such as chromatography, infrared spectroscopy, ultraviolet / visible spectroscopy, nuclear magnetic resonance analysis, X-ray diffraction and mass spectrometry, X-ray photoelectron spectroscopy, etc.

[0235] The content of the polymer in the second encapsulating layer is preferably in the range of 85 to 100% by mass, more preferably in the range of 90 to 95% by mass.

[0236] <Third Encapsulation Layer>

[0237] The third encapsulation layer is provided adjacent to the second encapsulation layer and is formed by the vapor phase method, and specifically, contains silicon nitride, silicon oxide (silicon monoxide, silicon dioxide, etc.), or silicon oxynitride, similarly to the first encapsulation layer.

[0238] [Electronic devices]

[0239] In the method for forming an electronic device encapsulation film and the electronic device encapsulation film of the present invention, the encapsulated electronic device may be, for example, an organic EL element, an LED element, a liquid crystal display element (LCD), a thin film transistor, a touch panel, an electronic paper, a solar cell (PV), etc. From the viewpoint of more effectively obtaining the effect of the present invention, an organic EL element, a solar cell or an LED element is preferred, and an organic EL element is particularly preferred.

[0240] <Organic EL devices>

[0241] The organic EL element used as the electronic device of the present invention may be a bottom emission type organic EL element, that is, an organic EL element that extracts light from the transparent substrate side.

[0242] Specifically, the bottom emission type is constituted by laminating a transparent electrode as a cathode, a light-emitting functional layer, and a counter electrode as an anode in this order on a transparent substrate.

[0243] The organic EL element of the present invention may be a top emission type, that is, an organic EL element that extracts light from a transparent electrode side serving as a cathode opposite to a substrate.

[0244] Specifically, the top emission type has a structure in which a counter electrode as an anode is provided on the substrate side, and a light-emitting functional layer and a transparent electrode as a cathode are sequentially stacked on the surface.

[0245] A typical example of the structure of an organic EL element is shown below.

[0246] (i) Anode / Hole injection and transport layer / Emitting layer / Electron injection and transport layer / Cathode

[0247] (ii) Anode / hole injection and transport layer / light-emitting layer / hole blocking layer / electron injection and transport layer / cathode

[0248] (iii) anode / hole injection and transport layer / electron blocking layer / light-emitting layer / hole blocking layer / electron injection and transport layer / cathode

[0249] (iv) Anode / hole injection layer / hole transport layer / light-emitting layer / electron transport layer / electron injection layer / cathode

[0250] (v) Anode / hole injection layer / hole transport layer / light-emitting layer / hole blocking layer / electron transport layer / electron injection layer / cathode

[0251] (vi) anode / hole injection layer / hole transport layer / electron blocking layer / light-emitting layer / hole blocking layer / electron transport layer / electron injection layer / cathode

[0252] Furthermore, the organic EL element may have a non-luminescent intermediate layer. The intermediate layer may be a charge generating layer or may be composed of a multiphoton unit.

[0253] As for the outline of the organic EL element applicable to the present invention, for example, Japanese Patent Application Laid-Open No. 2013-157634, Japanese Patent Application Laid-Open No. 2013-168552, Japanese Patent Application Laid-Open No. 2013-177361, Japanese Patent Application Laid-Open No. 2013-187211, Japanese Patent Application Laid-Open No. 2013-191644, Japanese Patent Application Laid-Open No. 2013-191804, Japanese Patent Application Laid-Open No. 2013-225678, Japanese Patent Application Laid-Open No. 2013-235994, Japanese Patent Application Laid-Open No. 2013- The configurations described in Japanese Patent Application Laid-Open No. 243234, Japanese Patent Application Laid-Open No. 2013-243236, Japanese Patent Application Laid-Open No. 2013-242366, Japanese Patent Application Laid-Open No. 2013-243371, Japanese Patent Application Laid-Open No. 2013-245179, Japanese Patent Application Laid-Open No. 2014-003249, Japanese Patent Application Laid-Open No. 2014-003299, Japanese Patent Application Laid-Open No. 2014-013910, Japanese Patent Application Laid-Open No. 2014-017493, Japanese Patent Application Laid-Open No. 2014-017494, etc.

[0254] <Base material>

[0255] As a substrate (hereinafter also referred to as a supporting substrate, base, substrate, support, etc.) that can be used for the above-mentioned organic EL element, specifically, glass or a resin film is preferably used. When flexibility is required, a resin film is preferably used.

[0256] In addition, it may be transparent or opaque. In the case of a so-called bottom emission type in which light is extracted from the substrate side, the substrate is preferably transparent.

[0257] Preferred resins include polyester resins, methacrylic resins, methacrylic acid-maleic acid copolymers, polystyrene resins, transparent fluorine resins, polyimides, fluorinated polyimide resins, polyamide resins, polyamide-imide resins, polyether-imide resins, cellulose acylate resins, polyurethane resins, polyether-ether-ketone resins, polycarbonate resins, alicyclic polyolefin resins, polyarylate resins, polyethersulfone resins, polysulfone resins, cycloolefin copolymers, fluorene ring-modified polycarbonate resins, alicyclic-modified polycarbonate resins, fluorene ring-modified polyester resins, acrylic compounds and other thermoplastic resins. The resins may be used alone or in combination of two or more.

[0258] The substrate is preferably made of a heat-resistant material. Specifically, a substrate having a linear expansion coefficient of 15 ppm / K to 100 ppm / K and a glass transition temperature (Tg) of 100°C to 300°C is used.

[0259] The substrate meets the necessary conditions for use in electronic components and as a laminated film for displays. That is, when the encapsulation film of the present invention is used in these applications, the substrate is sometimes exposed to a process above 150°C. In this case, if the linear expansion coefficient of the substrate exceeds 100ppm / K, the substrate size is unstable when passing through the process at the temperature described above, and it is easy to produce the undesirable situation of deterioration of the blocking performance or the undesirable situation of being unable to withstand the thermal process due to thermal expansion and contraction. When it is less than 15ppm / K, the film will break like glass, and there is a situation of deterioration of flexibility.

[0260] The Tg and linear expansion coefficient of the substrate can be adjusted by additives and the like.

[0261] More preferred specific examples of thermoplastic resins that can be used as the substrate include polyethylene terephthalate (PET: 70°C), polyethylene naphthalate (PEN: 120°C), polycarbonate (PC: 140°C), alicyclic polyolefins (e.g., ZEONOR (registered trademark) 1600 manufactured by Zeon Corporation: 160°C), polyarylate (PAr: 210°C), polyether sulfone (PES: 220°C), polysulfone (PSF: 190°C), cycloolefin copolymer (COC: described in Japanese Patent Application Laid-Open No. 2001-150584) and polyether sulfone (PES: 220°C). Compounds: 162°C), polyimides (e.g., Neopulim (registered trademark) manufactured by Mitsubishi Gas Chemical Co., Ltd.: 260°C), fluorene ring-modified polycarbonate (BCF-PC: compounds described in JP-A-2000-227603: 225°C), alicyclic modified polycarbonate (IP-PC: compounds described in JP-A-2000-227603: 205°C), acrylic compounds (compounds described in JP-A-2002-80616: 300°C or more), etc. (temperatures in parentheses represent Tg).

[0262] The electronic device of the present invention is an electronic device such as an organic EL element, so the substrate is preferably transparent. That is, the light transmittance is usually 80% or more, preferably 85% or more, and more preferably 90% or more. The light transmittance can be calculated by subtracting the diffuse transmittance from the total light transmittance by using the method described in JIS K7105:1981, that is, using an integrating sphere light transmittance measuring device to measure the total light transmittance and the amount of scattered light.

[0263] In addition, the substrates mentioned above can be unstretched films or stretched films. The substrates can be manufactured by conventional methods known in the past. Regarding the manufacturing methods of these substrates, the matters described in paragraphs "0051" to "0055" of International Publication No. 2013 / 002026 can be appropriately adopted.

[0264] The surface of the substrate may be subjected to various known treatments for improving adhesion, such as corona discharge treatment, flame treatment, oxidation treatment or plasma treatment, or the above treatments may be combined as required. In addition, the substrate may be subjected to an easy-adhesion treatment.

[0265] The substrate may be a single layer or a laminated structure of two or more layers. When the substrate has a laminated structure of two or more layers, each substrate may be of the same type or of different types.

[0266] The thickness of the substrate of the present invention (the total thickness in the case of a laminated structure of two or more layers) is preferably 10 to 200 μm, more preferably 20 to 150 μm.

[0267] In the case of a film substrate, a film substrate with a gas barrier layer is preferred.

[0268] The gas barrier layer for the film substrate may be formed as an inorganic film, an organic film or a mixed film of the two on the surface of the film substrate, and preferably has a water vapor permeability (25±0.5°C, relative humidity (90±2)%RH) of 0.01 g / m 2 The barrier film with a shelf life of 24 hours or less is more preferably an oxygen permeability of 1×10 -3 mL / m 2 ·24h·atm or less, water vapor transmission rate is 1×10 - 3 g / m 2 ·High gas barrier film for less than 24 hours.

[0269] The gas barrier layer may be formed of any material as long as it has the function of suppressing the infiltration of substances such as moisture and oxygen that cause element degradation, and for example, silicon monoxide, silicon dioxide, silicon nitride, silicon oxynitride, silicon carbide, silicon oxycarbide, etc. can be used.

[0270] The gas barrier layer is not particularly limited. For example, in the case of an inorganic gas barrier layer such as silicon monoxide, silicon dioxide, silicon nitride, silicon oxynitride, silicon carbide, or silicon oxycarbide, it is preferred to form a layer using a chemical vapor deposition method such as sputtering (for example, magnetron cathode sputtering, planar magnetron sputtering, diode AC planar magnetron sputtering, diode AC rotary magnetron sputtering, etc.), a vapor deposition method (for example, resistance heating vapor deposition, electron beam vapor deposition, ion beam vapor deposition, plasma assisted vapor deposition, etc.), thermal CVD, catalytic chemical vapor deposition (Cat-CVD), capacitively coupled plasma CVD (CCP-CVD), photo CVD, plasma CVD (PE-CVD), epitaxial growth, atomic layer deposition (ALD), reactive sputtering, and the like.

[0271] Furthermore, the inorganic gas barrier layer can also be formed by coating a coating liquid containing an inorganic precursor such as polysilazane, tetraethyl orthosilicate (TEOS) on a support and then performing a modification treatment such as irradiation with vacuum ultraviolet light to form an inorganic gas barrier layer, or by thin-film metallization techniques such as plating a metal on a resin substrate to bond a metal foil to the resin substrate.

[0272] In addition, the inorganic gas barrier layer may include an organic layer containing an organic polymer. In other words, the inorganic gas barrier layer may be a laminate of an inorganic layer containing an inorganic material and an organic layer.

[0273] The organic layer can be formed, for example, by coating an organic monomer or an organic oligomer on a resin substrate to form a layer, followed by polymerization and crosslinking as required using, for example, an electron beam device, a UV light source, a discharge device or other appropriate device. Alternatively, it can be formed, for example, by evaporating an organic monomer or an organic oligomer that can flash evaporate and crosslink with radiation, and then forming a polymer from the organic monomer or organic oligomer. The coating efficiency can be improved by cooling the resin substrate.

[0274] As the coating method of organic monomer or organic oligomer, for example, roll coating (for example gravure roll coating), spray coating (for example electrostatic spray coating) etc. can be enumerated. In addition, as the example of the laminate of inorganic layer and organic layer, for example, the laminate of record in International Publication No. 2012 / 003198 and International Publication No. 2011 / 013341 etc. can be enumerated.

[0275] In the case of a laminate of an inorganic layer and an organic layer, the thickness of each layer may be the same or different. The thickness of the inorganic layer is preferably in the range of 3 to 1000 nm, more preferably in the range of 10 to 300 nm. The thickness of the organic layer is preferably in the range of 100 nm to 100 μm, more preferably in the range of 1 to 50 μm.

[0276] Example

[0277] The present invention is specifically described below with reference to examples, but the present invention is not limited thereto. It should be noted that in the following examples, unless otherwise specified, the operation is performed at room temperature (25° C.). In addition, unless otherwise specified, “%” and “parts” represent “mass %” and “mass parts”, respectively.

[0278] [monomer]

[0279] The monomers used in the preparation of the encapsulating composition are as follows.

[0280] In addition, the number of (meth)acrylic acid groups of each monomer is shown in the following Table I. In the following Table I, the case of having an "acrylic acid group" is expressed as "0", and the case of having a "methacrylic acid group" is expressed as "1".

[0281]

[0282] [Table 1]

[0283] Table 1

[0284]

[0285] [Photopolymerization initiator]

[0286] The photopolymerization initiators used in the preparation of the encapsulating composition are shown in Table II below.

[0287] [Table 2]

[0288] Table II

[0289] Photopolymerization initiator No. Product Name B01 IGM Omnirad TPO B02 IGM Omnirad 184 B03 IGM Omnirad 819 B04 IGM Esacure 1001M B05 IGM Omnirad ITX B06 Omnirad DETX manufactured by IGM

[0290] [Preparation of Encapsulating Compositions 1 to 38]

[0291] Each monomer was weighed under a nitrogen atmosphere so as to have the type and mass fraction shown in Table III below, thereby obtaining monomer preparation liquids 1 to 7.

[0292] Furthermore, a photopolymerization initiator was added to each of these monomer preparation solutions 1 to 7 in the types and mass parts shown in Table IV below, placed in a brown bottle, and stirred on a hot plate at 65° C. for 3 hours to obtain each of encapsulating compositions 1 to 38.

[0293] [Table 3] Table II@

[0294]

[0295] [Table 4]

[0296] Table IV

[0297]

[0298] <Average number of (meth)acrylic acid groups and methacrylate ratio>

[0299] For each encapsulating composition, the average number of (meth)acrylic acid groups and the methacrylate ratio were calculated from the following formula and are shown in the above Table IV.

[0300] The average number of (meth)acrylic acid groups is calculated as follows using the number n of (meth)acrylic acid groups contained in the monomer and the mass ratio w when the total mass of the monomers is taken as 1.

[0301] Average number of (meth)acrylic acid groups = n1×w1+n2×w2+···

[0302] (The subscripts n and w indicate the monomer number.)

[0303] The methacrylate ratio is calculated as follows using the total mass wm of monomers having a methacrylic group and the total mass wa of monomers having an acrylic group.

[0304] Methacrylate ratio (%) = wm / (wa+wm)×100

[0305] <Residue rate>

[0306] In a nitrogen environment, a coating film of the encapsulation composition with a thickness of 10 μm was formed on a glass substrate having a size of 50 mm×50 mm. The coating film was heated at 300 mW / cm 2 The ultraviolet light with a wavelength of 395 nm (MZ240mm 395 nm UV LED manufactured by IST) was irradiated to a cumulative light intensity of 1.5 J / cm 2 , so that the coating film is cured. 10 mg of the obtained cured film was recovered with a spatula, and the temperature was raised to 500°C at a heating rate of 10°C / min in a nitrogen atmosphere using a TG-DTA device (Thermo Plus EVO2 manufactured by Rigaku Corporation). Then, the residue rate was calculated by the following formula based on the mass w at 500°C relative to the initial mass w0.

[0307] Residue rate (%) = w / w0 × 100 (%)

[0308] (Residue rate = (1-mass reduction rate) × 100, mass reduction rate = 1-w / w0)

[0309] <Curing rate>

[0310] In a nitrogen environment, a coating film of the encapsulation composition with a thickness of 10 μm was formed on a glass substrate having a size of 50 mm×50 mm. The coating film was heated at 300 mW / cm 2 The ultraviolet light with a wavelength of 395 nm (MZ240mm 395 nm UV LED manufactured by IST) was irradiated to a cumulative light intensity of 1.5 J / cm 2 The coating film was cured. The obtained cured film (encapsulation film) and the composition before curing were measured by FTIR (infrared spectrophotometer Nexus 870). According to the obtained spectrum, the peak derived from the C=C bond of the (meth)acryloyl group (810 cm -1 ) strength, and the curing rate is calculated by the following formula.

[0311] Curing rate (%) = (1-a / b) × 100

[0312] a: Peak value derived from C=C bond of the encapsulating composition before curing

[0313] b: Peak from C=C bond of the cured encapsulation film

[0314] [evaluate]

[0315] <Rate of change of relative dielectric constant>

[0316] A 150 nm thick ITO film was formed on a 50 mm × 50 mm glass substrate by sputtering. Then, a 10 μm thick film of the encapsulation composition was prepared in a nitrogen environment. The film was heated at 300 mW / cm2 The ultraviolet light with a wavelength of 395 nm (MZ 240 mm 395 nm UV LED manufactured by IST) was irradiated to a cumulative light intensity of 1.5 J / cm 2 The coating was cured to prepare a sample for measurement. An Ag film was formed on the evaluation sample by sputtering, and impedance was measured by an impedance measuring device (Solartron 126096) at a frequency of 100 kHz and AC 0.1 (V). The relative dielectric constant obtained was taken as the initial relative dielectric constant.

[0317] Next, the evaluation sample was stored at 85°C and 85% RH for 72 hours, and then an Ag film was formed by sputtering. The relative dielectric constant was measured by impedance measurement using an impedance measurement device (Solartron 126096) at a frequency of 100 kHz and AC 0.1 (V). The relative dielectric constant obtained was taken as the relative dielectric constant after storage.

[0318] The rate of change of the relative dielectric constant was calculated from the initial relative dielectric constant and the relative dielectric constant after storage using the following formula.

[0319] Change rate of relative dielectric constant (%) = (initial relative dielectric constant - relative dielectric constant after storage) ÷ initial relative dielectric constant × 100

[0320] <Stability of relative dielectric constant>

[0321] Based on the change rate of the relative dielectric constant calculated above, the stability of the relative dielectric constant was evaluated according to the following criteria: Levels 2 to 4 were evaluated as passing.

[0322] (Benchmark)

[0323] Level 1: 15% or more

[0324] Level 2: 10% or more and less than 15%

[0325] Level 3: 5% or more and less than 10%

[0326] Level 4: Less than 5%

[0327] <Adhesion>

[0328] Silicon nitride (SiNx) with a thickness of 500 nm was formed on a glass substrate with a size of 50 mm×50 mm by plasma CVD. Then, a coating film of a composition for encapsulation with a thickness of 10 μm was prepared in a nitrogen environment. The coating film was heated at 300 mW / cm 2 The ultraviolet light with a wavelength of 395 nm (MZ 240 mm 395 nm UV LED manufactured by IST) was irradiated to a cumulative light intensity of 1.5 J / cm2 , and the coating film is cured to prepare a test sample. A tape (#600 manufactured by 3M Company) is attached to the test sample and allowed to stand for 24 hours. Then, the tape is peeled off at 180 degrees, and the adhesion (N / inch) between the silicon nitride and the cured film (encapsulation film) of the encapsulation composition is determined according to the following criteria. Grades 2 to 4 are evaluated as qualified.

[0329] (Benchmark)

[0330] Level 1: less than 0.1N / inch

[0331] Level 2: 0.1N / inch or more and less than 1.0N / inch

[0332] Level 3: 1.0N / inch or more and less than 4.0N / inch

[0333] Level 4: 4.0N / inch or more

[0334] [Table 5]

[0335] Table V

[0336]

[0337] As shown in the above results, it is understood that the encapsulating composition of the present invention has better stability of relative dielectric constant and better adhesion than the encapsulating composition of the comparative example.

[0338] Industrial Applicability

[0339] The present invention can be used for a composition for electronic device encapsulation, an electronic device encapsulation film, and a method for forming an electronic device encapsulation film, which can provide an electronic device encapsulation film having excellent relative dielectric constant stability and adhesion.

Claims

1. A composition for encapsulating an electronic device, comprising a photopolymerizable monomer and a photopolymerization initiator, contains (meth)acrylate as the photopolymerizable monomer, In nitrogen environment, 1.5 J cm -2 When cured by irradiation with ultraviolet rays having a wavelength of 395 nm, the formed electronic device encapsulation film has a curing rate of 80% or more, and a residue rate measured by TG-DTA of the electronic device encapsulation film is 3% or more.

2. The composition for electronic device encapsulation according to claim 1, wherein The above-mentioned curing rate is 90% or more.

3. The composition for electronic device encapsulation according to claim 1, wherein The above-mentioned residue rate is 5% or more.

4. The composition for electronic device encapsulation according to claim 1, wherein The above-mentioned residue rate is 10% or more.

5. The composition for electronic device encapsulation according to claim 1, wherein In nitrogen environment, 1.5 J cm -2 When cured by irradiation with ultraviolet rays having a wavelength of 395 nm, the resulting electronic device encapsulation film has a relative dielectric constant of 3.1 or less.

6. The composition for electronic device encapsulation according to claim 1, wherein The average number of (meth)acrylic groups of the photopolymerizable monomer contained in the composition for encapsulating electronic components is within a range of 1.3 to 1.

5.

7. The composition for electronic device encapsulation according to claim 1, wherein The methacrylate ratio of the photopolymerizable monomer contained in the composition for encapsulating electronic components is within a range of 50 to 80%.

8. An electronic device encapsulating film, which is an electronic device encapsulating film obtained by encapsulating an electronic device by curing a composition for encapsulating an electronic device containing a photopolymerizable monomer and a photopolymerization initiator, contains (meth)acrylate as the photopolymerizable monomer, The curing rate of the electronic device packaging film is above 80%, and The electronic device encapsulation film has a residue rate of 3% or more as measured by a differential thermal-thermogravimetric simultaneous measurement apparatus (TG-DTA).

9. An electronic device packaging film is an electronic device packaging film for packaging electronic devices, having: The first encapsulation layer comprises silicon nitride, silicon oxide or silicon oxynitride, and The second encapsulating layer uses the composition for encapsulating an electronic device according to any one of claims 1 to 7.

10. The electronic device packaging film according to claim 9, wherein: A third encapsulation layer including silicon nitride, silicon oxide or silicon oxynitride is provided on the second encapsulation layer.

11. A method for forming an electronic device encapsulating film, the method comprising: The process of forming a first encapsulation layer on the electronic device by a vapor phase method, and A step of forming a second encapsulating layer by applying the electronic component encapsulating composition onto the first encapsulating layer.

12. The method for forming an electronic device packaging film according to claim 11, wherein: The method comprises the step of forming a third encapsulation layer on the second encapsulation layer by a vapor phase method.

13. The method for forming an electronic device packaging film according to claim 11, wherein: The second encapsulation layer is formed by an inkjet method.

Citation Information

Patent Citations

  • Liquid crystal display device and transparent conductive substrate suitable for the same

    JP2000227603A

  • Conductive substrate, and display element using the same

    JP2001150584A

  • Polymer film for display element and substrate for display element using the same

    JP2002080616A

  • Organic electroluminescent element material

    JP2013157634A

  • Organic electroluminescent element, and display device and lighting device including the same

    JP2013168552A